Analysis of the Role of Regional Government in Optimizing the School Operational Assistance Program (BOSP) Policy in Surabaya as a Strategy for Improving Education Quality - Dewi, Rahmatika Putri; Pramudiana, Ika Devy; Widyawati, Widyawati; Patria, Dendy (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
The development of the implementation of the School Operational Assistance Policy (BOSP) in Surabaya faces various challenges that affect policy optimization. This study aims to analyze the role of local government in optimizing the BOSP policy using Edward III's policy implementation theory, which includes communication, bureaucratic structure, resources, and the disposition or attitudes of implementers. This research employs a qualitative method by collecting data through in-depth interviews with informants from the education office and educational institutions in Surabaya, as well as documentation studies related to the BOSP policy. The study results show that communication contributes 68% to the success of the BOSP policy implementation, although there are still shortcomings in responsiveness and socialization. Bureaucratic structure contributes 72%, with major challenges in fragmented coordination between units and complex decision-making procedures. Resources contribute the highest at 74%, but limitations in staff competence and technological infrastructure remain significant obstacles. The disposition or attitudes of implementers contribute 73% to success, though deficiencies in discipline, integrity, and initiative are still evident. These four aspects indicate that while most elements have performed well, there is still room for improvement requiring serious attention to enhance policy effectiveness.The conclusion of this study is that optimizing the BOSP policy in Surabaya requires strengthening the four analyzed aspects. To address communication shortcomings, more structured and responsive socialization mechanisms are needed. Bureaucratic fragmentation can be resolved by simplifying procedures and integrating data management systems. Human resource and technological limitations must be addressed through intensive training and infrastructure investment. Finally, implementer disposition can be improved through development programs and supervision. These strategic recommendations can support the Surabaya local government in optimizing the implementation of the BOSP policy in a transparent, accountable, and effective manner to achieve better educational goals.